A comparison of the accuracy of the corpuscular fragility and mean corpuscular volume tests for the alpha-thalassemia 1 and beta-thalassemia traits - Sirichotiyakul S. (2014)
Objective: To compare the accuracy of the osmotic fragility test (OFT) and mean corpuscular volume (MCV) calculation when screening for the α-thalassemia 1 and/or β-thalassemia trait. Method: In this cross-sectional study, blood samples from 328 apparently healthy pregnant women were sent on the same day to separate laboratories for the OFT (performed using a glycerol 0.45%, phosphate-buffered, sodium chloride solution) and MCV testing (by means of a standard automated hematology analyzer). A polymerase chain reaction was also performed to positively diagnose α-thalassemia 1 carriers, and a quantitative HbA2 test to positively diagnose β-thalassemia carriers. Results: Sensitivity and specificity were 95.0% and 86% for the OFT; and based on the cut-off point of 78.1 fL derived from the ROC curve, they were 93% and 93.4% for MCV calculation. The latter test was found to be slightly more accurate than the OFT in predicting the presence of the α-thalassemia 1 and/or β-thalassemia trait. Conclusion: Both tests have high screening sensitivity for the α-thalassemia 1 and/or β-thalassemia traits, and their simplicity and very low cost make them attractive as screening tests for large populations. Since MCV seems to provide fewer false-positive results, it may be the first choice wherever an automated hematology analyzer calculating MCV is available. © 2009.